'State-Security First' and the Militarization of Development: Local Perceptions on Post-Conflict Reconstruction Policies in Pakistan's Tribal Areas (2015–2019). Issue 2 (4th May 2021) - Dawar, Asif Iqbal; Ferreira, Marcos Farias
Abstract: In the post-military operation scenario, the government of Pakistan (GoP) has launched reconstruction interventions under the notion of 'build back better and smarter'. This article critically evaluates the reconstruction efforts (2015–2019) using local perceptions to attest as to what extent reconstruction interventions have been participatory and how they have been received by local communities in terms of their contextual needs. Primary data was collected during 2017–2019 in North Waziristan (NW) through semi-structured interviews, informal discussions and participant observation with local and key respondents. The study found that although interventions were designed predominantly to improve development outcomes and build connections between local community and the state, the 'state-security first' paradigm reigns over the 'positive security' of the affected population. Interventions were centrally planned without proper participation or even taking into account local needs and grievances. The article argues that instead post-conflict reconstruction policies and practices should focus on well-assessed micro-needs, confidence-building approaches and the participation of local communities in order to achieve the desired goals of positive security and sustainable development.